2023
DOI: 10.3390/antiox12030640
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 3 Inhibits 3T3-L1 Adipocyte Differentiation via Reduction of Reactive Oxygen Species

Abstract: Metallothionein 3 (MT3), also known as a neuronal growth-inhibitory factor, is a member of the metallothionein family and is involved in a variety of biological functions, including protection against metal toxicity and reactive oxygen species (ROS). However, less is known about the role of MT3 in the differentiation of 3T3-L1 cells into adipocytes. In this study, we observed that MT3 levels were downregulated during 3T3-L1 adipocyte differentiation. Mt3 overexpression inhibited adipocyte differentiation and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…Numerous studies have suggested that MT3 is an important redox protein and that its cysteine sulfhydryl group releases hydrogen to bind oxygen radicals, thereby reducing reactive oxygen species (ROS) in cells such as osteoblast or adipocytes 40 , 41 , and ROS production plays a critical role in PH 42 . However, whether MT3 affects ROS production in PASMCs during PH has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have suggested that MT3 is an important redox protein and that its cysteine sulfhydryl group releases hydrogen to bind oxygen radicals, thereby reducing reactive oxygen species (ROS) in cells such as osteoblast or adipocytes 40 , 41 , and ROS production plays a critical role in PH 42 . However, whether MT3 affects ROS production in PASMCs during PH has not been reported.…”
Section: Resultsmentioning
confidence: 99%